2016
DOI: 10.1038/srep34045
|View full text |Cite
|
Sign up to set email alerts
|

Sweeter and stronger: enhancing sweetness and stability of the single chain monellin MNEI through molecular design

Abstract: Sweet proteins are a family of proteins with no structure or sequence homology, able to elicit a sweet sensation in humans through their interaction with the dimeric T1R2-T1R3 sweet receptor. In particular, monellin and its single chain derivative (MNEI) are among the sweetest proteins known to men. Starting from a careful analysis of the surface electrostatic potentials, we have designed new mutants of MNEI with enhanced sweetness. Then, we have included in the most promising variant the stabilising mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…Analysis of variance results (Table ) showed that the sweeteners did not differ for almost every parameter extracted from the t – I curves ( I start , I end , I max , t start , t SPl , t EPl ) ( p > 0.05), except for t end ( p ≪ 0.01), which ranged between 42 and 50 s, for xylitol, sucrose, and sorbitol, without significant differences among these sweeteners, to 66 s, for MNEI. These results indicate that the sweetness imparted by MNEI ended almost 20 s later compared to the other sweeteners in stirred yogurts, hinting to a different mechanism of interaction between the protein and sweet taste receptors, already underlined in previous studies (Di Monaco et al, ; Leone et al, ; Miele, Cabisidan, Galiñanes Plaza, et al, ).…”
Section: Resultssupporting
confidence: 61%
“…Analysis of variance results (Table ) showed that the sweeteners did not differ for almost every parameter extracted from the t – I curves ( I start , I end , I max , t start , t SPl , t EPl ) ( p > 0.05), except for t end ( p ≪ 0.01), which ranged between 42 and 50 s, for xylitol, sucrose, and sorbitol, without significant differences among these sweeteners, to 66 s, for MNEI. These results indicate that the sweetness imparted by MNEI ended almost 20 s later compared to the other sweeteners in stirred yogurts, hinting to a different mechanism of interaction between the protein and sweet taste receptors, already underlined in previous studies (Di Monaco et al, ; Leone et al, ; Miele, Cabisidan, Galiñanes Plaza, et al, ).…”
Section: Resultssupporting
confidence: 61%
“…High thermal stability makes both protein storage and handling easier and allows some high‐temperature reactions. A wide number of experimental and theoretical approaches have been developed aimed at engineering proteins endowed with a remarkable thermal stability . However, a full comprehension of the basic principles that govern protein thermal stability represents one of the main goals of structural biology.…”
Section: Discussionmentioning
confidence: 99%
“…Most mutational studies have aimed to shed light on the interaction of monellin and the sweet taste receptor though some also intend to increase the stability of the protein. Mutation E23Q increased the sweet taste of monellin 50 . A variant of the E23Q mutant with increased stability was constructed by Leone et al .…”
Section: Discussionmentioning
confidence: 98%
“…Sweet assessment studies have shown that the substitution of arginine 39 with glutamic acid or aspartic acid produced mutants with detection thresholds at 13 000 nM and 89 000 nM, respectively 49 . According to the “wedge model” R39 together with D7, R88 and R65 are crucial to retain sweetness 50 . Our findings correlates well with the wedge model in which arginine 39 interacts with the sweet taste receptor while serine 76 is situated far away from the interaction site 32 .…”
Section: Discussionmentioning
confidence: 99%